Non‐Double‐Couple Microearthquakes in the Focal Area of the 2000 Western Tottori Earthquake (M 7.3) via Hyperdense Seismic Observations - Yuto Hayashida; Satoshi Matsumoto; Yoshihisa Iio; Shin'ich Sakai; Aitaro Kato (Geophysical Research Letters, 2020)
Abstract Earthquakes with non‐double‐couple (NDC) components are indicators of geometric fault complexity, anisotropy, tensile failure, and fluid flow effects. NDC earthquakes have been observed in volcanic zones and interpreted as faulting related to fluid effects in the hypocentral region. In this study, we provide evidence of the occurrence of microearthquakes with NDC components in a tectonic zone. Aftershocks of the 2000 Western Tottori earthquake revealed definite NDC components based on a polarity analysis of the first P wave motion data from a hyperdense seismic observation. We modeled these events using both shear faulting with tensile failure and multiple shear ruptures. Six of the eight NDC events were well modeled by shear faults accompanied with an opening tensile crack. These results suggest that pressurized fluid or a weak tensile crack may exist along the rupture zone of the Tottori earthquake.